A atuação docente na zona rural de Iranduba, Amazonas: um estudo sobre o uso das tecnologias digitais da informação e comunicação no ensino médio presencial com mediação tecnológica - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
This dissertation aimed to analyze the impact of technology usage on the teaching profile of high school education in the face-to-face modality with technological mediation, considering the changes implemented by the new high school curriculum and the specificities of rural areas in the state of Amazonas, particularly in the municipality of Iranduba. Additionally, it sought to identify the integration of technologies into the teaching professional profile, as well as their perception of digital culture, evaluating the adequacy of the teaching profile to technological advances. The methodology employed data triangulation to achieve maximum depth in describing the object of study. Norbert Elias provides the main analyses of this dissertation, becoming the central theoretical-methodological reference. The results demonstrate the extent to which the authorities responsible for deliberating public policies for education in Brazil and the Amazon Region need to progress in effectively applying technology to education in rural communities. However, before anything else, a precise diagnosis of the reality of these communities and the education professionals working in them is essential. Understanding their specificities is crucial for public policies and academic and continuing education programs to be effective in this vast region with so many diverse communities within the Amazon.
Keywords: CIENCIAS HUMANAS; Tecnologia; Educação; Atuação Docente; Ensino Presencial Mediado por Tecnologia